Practical Implication of Zakat in Socio-economic Empowerment during the COVID-19 Pandemic - Meliana Eka Puji Lestari; Cenny Sanita Febiyanti; Muhammad Riyal Abdul Rohman; Adilnia Fifi Susanti; Fahmi Medias; Fella Shasmita Hani Annisaa’ (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The extent to which zakat has contributed to and been implicated in the socio-economic empowerment of Muslim countries has not been the subject of a literature review. This study analyzes the practical implications of zakat in the OIC countries during the COVID-19 pandemic from the existing literature. Data were obtained from Harzing's Publish or Perish to analyze the role of zakat involvement in the socio-economic community in OIC countries from 2019 to 2021. 31 scholarly studies on the topics of economics, health, and education illustrate the economic implications of zakat. The discussion on the implications of zakat includes poverty reduction, economic empowerment, and MSMEs improvement. Zakat helps to fund community health care. Zakat provides educational scholarships, and school infrastructure, and enhances the feasibility of school arrangements. This study could assist the government to recognize the importance of zakat for socioeconomic empowerment and help policymakers develop strategic strategies to increase zakat participation, particularly in Muslim countries.